Coffee, tea, chocolate, and the brain (CRC Press, 2004)
Coffee, tea, and chocolate are among the most frequently consumed products in the world. The pleasure that many experience from these edibles is accompanied by a range of favorable and adverse effects on the brain that have been the focus of a wealth of recent research.